Responses of foliar phosphorus fractions to soil age are diverse along a 2 Myr dune chronosequence - Yan, Li; Zhang, Xinhou; Han, Zhongming; Pang, Jiayin; Lambers, Hans; Finnegan, Patrick M. (The New phytologist, 2019)
Plants respond to soil phosphorus (P) availability by adjusting leaf P among inorganic P (Pi) and organic P fractions (nucleic acids, phospholipids, small metabolites and a residual fraction). We tested whether phylogenetically divergent plants in a biodiversity hotspot similarly adjust leaf P allocation in response to P limitation by sampling along a 2 Myr chronosequence in southwestern Australia where nitrogen (N) limitation transitions to P limitation with increasing soil age. Total P and N, and P allocated to five chemical fractions were determined for photosynthetic organs from Melaleuca systena (Myrtaceae), Acacia rostellifera (Fabaceae) and Hakea prostrata (Proteaceae). Soil characteristics were also determined. Acacia rostellifera maintained phyllode total P and N concentrations at c. 0.5 and 16 mg g−1 DW, respectively, with a constant P-allocation pattern along the chronosequence. H. prostrata leaves allocated less P to Pi, phospholipids and nucleic acids with increasing soil age, while leaf N concentration was constant. M. systena had the greatest variation in allocating leaf P, whereas leaf N concentration decreased 20% along the chronosequence. Variation in P-allocation patterns was only partially conserved among species along the chronosequence. Such variation could have an impact on species distribution and contribute to species richness in P-limited environments.